Perspektif Kritis Jamal Khashoggi dalam artikel Washington Post terhadap kebijakan Arab Saudi - Rahmat Firnanda (Kalam: Jurnal Agama dan Sosial Humaniora, 2021)
A critical perspective of Jamal Khashoggi towards the Saudi Arabia policy is part of the free expression which Khashoggi expected can be implemented in his homeland Saudi. The dispute in defining a narration between the Saudi government and Khashoggi toward to some policy Saudi took caused of his departure to Washington DC and started to voice his critics and opinions by writing articles in Washington Post from 2017 until 2018. The issues which he touched on were about free expression, the Yemen war, corruption, and Ikhwanul Muslimin. This paper attempts to understand the problem Saudi faces which he wants to criticize on Saudi moves whether it is a domestic or foreign policy through qualitative narrative. This paper attempts to answer what are the big issues Khashoggi tries to deliver in the Washington Post articles he wrote. It can be found there are many detailed issues which Khashoggi has a different opinion to what Saudi has done under MBS. The reform that Saudi promise only applied to infrastructure. Ironically it is not followed by reform in free expression, free speech, and political rights for Saudi citizens as equality before the law.